Synthesis, characterization and DNA interaction studies of new triptycene derivatives - Chakraborty, Sourav; Mondal, Snehasish; Kumari, Rina; Bhowmick, Sourav; Das, Prolay; Das, Neeladri (Beilstein Journal of Organic Chemistry, 2014)
A facile and efficient synthesis of a new series of triptycene-based tripods is being reported. Using 2,6,14- or 2,7,14-triaminotriptycenes as synthons, the corresponding triazidotriptycenes were prepared in high yield. Additionally, we report the transformation of 2,6,14- or 2,7,14-triaminotriptycenes to the corresponding ethynyl-substituted triptycenes via their tribromo derivatives. Subsequently, derivatization of ethynyl-substituted triptycenes was studied to yield the respective propiolic acid and ethynylphosphine derivatives. Characterization of the newly functionalized triptycene derivatives and their regioisomers were carried out using FTIR and multinuclear NMR spectroscopy, mass spectrometry, and elemental analyses techniques. The study of the interaction of these trisubstituted triptycenes with various forms of DNA revealed interesting dependency on the functional groups of the triptycene core to initiate damage or conformational changes in DNA.
Keywords: abasic site; DNA damage; ethynyl; pUC19 plasmid; triptycene tripod